The effectiveness of peroneal nerve functional electrical simulation for the reduction of bradykinesia in Parkinson's disease: A feasibility study for a randomised control trial. (April 2021) - Taylor, Paul N; Sampson, Trish; Beare, Ben; Donavon-Hall, Maggie; Thomas, Peter W; Marques, Elsa; Strike, Paul; Seary, Coralie; Stevenson, Valerie L; Padiachy, Diran; Lee, James; Nell, Sheila
Objectives: To assess the feasibility of a multi-site randomised controlled trial to evaluate the effect of functional electrical stimulation on bradykinesia in people with Parkinson's disease. Design: A two-arm assessor blinded randomised controlled trial with an 18 weeks intervention period and 4 weeks post-intervention follow-up. Setting: Two UK hospitals; a therapy outpatient department in a district general hospital and a specialist neuroscience centre. Participants: A total of 64 participants with idiopathic Parkinson's disease and slow gait <1.25 ms −1 . Interventions: Functional electrical stimulation delivered to the common peroneal nerve while walking in addition to standard care compared with standard care alone. Main measures: Feasibility aims included the determination of sample size, recruitment and retention rates, acceptability of the protocol and confirmation of the primary outcome measure. The outcome measures were 10 m walking speed, Unified Parkinson's Disease Rating Scale (UPDRS), Mini Balance Evaluation Systems Test, Parkinson's Disease Questionnaire-39, EuroQol 5-dimension 5-level, New Freezing of Gait questionnaire, Falls Efficacy Score International and falls diary. Participants opinion on the study design and relevance of outcome measures were evaluated using an embedded qualitative study. Results: There was a mean difference between groups of 0.14 ms −1 (CI 0.03, 0.26) at week 18 in favour of the treatment group, which was maintained at week 22, 0.10 ms −1 (CI –0.05, 0.25). There was a mean difference in UPDRS motor examination score of –3.65 (CI –4.35, 0.54) at week 18 which was lost at week 22 –0.91 (CI –2.19, 2.26). Conclusion: The study design and intervention were feasible and supportive for a definitive trial. While both the study protocol and intervention were acceptable, recommendations for modifications are made.